Trends in Medical Imaging Safety Incidents: A Retrospective Analysis of Contributing Factors - Ibrahim P. Hussin; Sumayah Jaha; Fahad M. Al Mutairi; Mubarak K. Hilaby; Ayman Ahmad; Yasser H. Hadi; Marites C. Hussin (Dr. Sulaiman Al Habib Medical Journal)
Objectives: Patient safety is a cornerstone of healthcare quality, with incident reporting systems essential for fostering a safety culture. Despite the critical role of medical imaging, safety incidents remain a persistent challenge. This study analyzes trends and contributing factors in imaging safety incidents utilizing electronic occurrence variance reporting (OVR) data to identify patterns and recommend improvements. Methods: Data from the medical imaging department of a tertiary medical center’s OVR system were analyzed for incidents reported between 2021 and 2023. Incidents were categorized into four types: staff-related, equipment-related, intravenous access and administration–related, and patient-related events. Statistical analyses included descriptive statistics to assess the frequencies and types of incidents, Pearson’s correlation to evaluate the relationship between incident frequency and severity, and a one-sample t-test to identify changes in incident frequency over the study period. Results: Staff-related incidents declined from 76.47% in 2021 to 61.54% in 2023 (P = 0.02), whereas equipment-related incidents increased significantly from 10.29% to 24.62% (P = 0.03). Miscommunication emerged as the primary factor in staff-related incidents. While statistical analysis showed no significant correlation between incident frequency and severity (P = 0.536), a significant difference in incident frequency across the years was observed (P = 0.009). The rise in minor and moderate risk levels over time highlights the need for targeted risk management strategies. Conclusion: By analyzing trends in medical imaging safety incidents, this study provides actionable strategies to minimize risks and improve patient safety. Sustained efforts in communication, process optimization, and the cultivation of a safety-oriented culture are critical for preventing future incidents.